Performance Analysis of Transmit Diversity STBC-OFDM and Differential STBC-OFDM Over Fading Channels - Mohamed, Emad M. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: Alamouti space-time block coding (A-STBC) is a relatively well known coding technique that is employed to enhance the capacity of wireless communication systems without affecting the bandwidth efficiency. Furthermore, A-STBC is known to have a linear decoding complexity which has made it one of the most popular among space time codes (STCs). The decoding of space-time block codes, however, requires knowledge of channel state information (CSI) at the receiver and in general, channel parameters are assumed to be known (assumes that channel estimation is possible). However, when there is high mobility and the channel conditions are fluctuating rapidly it may be difficult to obtain perfect or close to perfect estimates for the channel. To alleviate this problem another space-time block coding technique known as Differential Space-Time Block Coding (DSTBC) has been proposed. Differential phase shift keying (DPSK) which is employed by DSTBCs is a common form of phase modulation that conveys data by changing the phase of the carrier wave. The decoder in DPSK modulation does not require CSI since the transmitted symbols depend on the previous symbol and the decoder would sense the data from symbols that come one after another. When channel fluctuations are very high DSTBCs need to be used at the expense of lower bit error rate. The work presented herein, provides a link level bit error rate analysis of none line- of-sight (NLOS) Alamouti space-time block coded with Orthogonal Frequency Division Multiplexing (OFDM) using either BPSK or QPSK modulation. OFDM is a multicarrier modulation technique where a high rate data stream is sub-divided into a number of lower rate data streams and transmitted over a number of subcarriers. The performance increment due to OFDM comes from the fact that the usage of a guard interval that help reduce or completely eliminate the interference between symbols due to multipath effect. The simulation results presented in this thesis have all been obtained using the readily available MATLAB platform and writing dedicated functions for different tasks. The results have been presented in four parts. The first part provides the bit error rate performance for BPSK modulated data transmitted over a Rayleigh fading channel. This is then followed by a performance analysis of OFDM over the AWGN channel using either BPSK or QPSK modulation. Third part demonstrates the BER vs. SNR for Alamouti STBC and Alamouti DSTBC coded data transmitted over a Rayleigh fading channel without using OFDM. Finally, part four will provide STBC and DSTBC coded OFDM performance when BPSK and QPSK are the preferred modulation and the channel is again the Rayleigh fading channel. The work presented clearly demonstrates that even though OFDM by itself is giving good performance by mitigating inter-symbol interference, combining OFDM with a transmit diversity technique like Alamouti STBC helps further improve the link level BER performance. The simulation results indicate that when no CSI is available and DSTBC needs to be employed, the system performance will degrade approximately by 2.2dB at a BER of 10-4 (in comparison to STBC-OFDM using BPSK). Keywords: STBC, DSTBC, OFDM, Rayleigh Fading, BER. ………………………………………………………………………………………………………………………… ÖZ: Alamouti uzay-zaman blok kodlama yöntemi (A-UZBK) nispeten iyi tanınan ve bant genişliği verimini etkilemeksizin kablosuz iletişim kapasitesini artırmak üzere yararlanılan bir yöntemdir. Buna ek olarak A-UZBK çözücüsünün doğrusal bir kod çözme karışıklığına sahip oluşu da bu yöntemi diğer uzay-zaman kodlayıcılar arasında öne çıkarmaktadır. Genellikle Alamouti uzay-zaman blok kodlama tekniğinin kod çözücüsü kanal durum bilgilerinin (KDB) bilinmesini gerektirmektedir ki bu da kanal tahmininin mümkün olduğu varsayımını gerektirir. Fakat yüksek hareketlilik oranının bulunduğu ve kanal koşullarının hızlı bir dalgalanma gösterdikleri durumlarda kanal için mükemmel veya mükemmele yakın tahminlerin elde edilmesi zorlaşabilmektedir. Bu problemin hafifletilmesi için Fark-Kodlamalı Uzay-Zaman Blok Kodlama (FK-UZBK) yöntemi önerilmiştir. FK-UZBK’lar tarafından kullanılan diferansiyel faz değiştirme anahtarlama (DPSK) yöntemi, taşıyıcı dalganın fazını değiştirerek verileri ileten yaygın bir faz geçiş şeklidir. İletilen semböller bir önceki semböle bağlı olup şifre çözücü verileri birbiri ardına gelen semböllerden algıladığından DPSK modülasyondaki şifre çözücü KDB’ni gerektirmemektedir. Kanal dalgalanmalarının yüksek olduğu durumlarda FK-UZBK’ların daha düşük bit hata oranı pahasına kullanılması bir zorunluluk olmaktadır. Bu çalışmada, Alamouti uzay-zaman blok kodlarıyla ikili ve dörtlü faz kaydırmalı kipleme kullanan Dikgen Frekans Bölüşümlü Çoğullama (DFBÇ) yöntemi birleştirilerek görüş hattı dışındaki (NLOS) durumlar için link seviyesinde bit hata oranı analizi gerçekleştirilmiştir. DFBÇ, yüksek hızlı veri akışına sahip bir katarın daha düşük hızlardaki birden fazla katara bölündüğü ve birçok alt taşıyıcı üzerinden aktarma yapılan çoklu taşıyıcılı bir modülasyon tekniğidir. DFBÇ’deki performans artışı, çoklu yol etkisinden kaynaklanan semböller arası karışmaların azaltılması veya tamamen ortadan kaldırılmasına yardımcı olan bir koruma bandının (çevrimsel öntakı) kullanımı ile sağlanmaktadır. Bu tez çalışmasında sunulan tüm benzetim sonuçları MATLAB platformunu kullanarak ve gerekli tüm görevler için adanmış fonksiyonlar yazarak elde edilmiştir. Sonuçlar dört bölüm halinde sunulmuştur. İlk bölüm, ikili faz kaydırmalı kiplenmiş verinin bir Rayleigh kanalı üzerinde göndrildiği durumlardaki bit hata oranı verimini sunmaktadır. Daha sonra ikinci bölümde ikili ve dörtlü faz kaydırmalı kipleme kullanan DFBÇ’nin Toplanır Beyaz Gauss Gürültü (TBGG) kanal üzerindeki performansı incelenmiştir. Üçüncü bölümde DFBÇ kullanılmadan yavaş sönümlemeli bir Rayleigh kanalı üzerinden aktarılan Alamouti UZBK ve Alamouti FK-UZBK ile kodlanmış veriler için bit-hata-oranı karşılaştırma sonuçları sunulmaktadır. Son olarak dördüncü bölüm ikili ve dörtlü faz kaydırmalı kipleme tekniklerinin tercih edildiği ve kanalın yine yavaş sönümlemeli bir Rayleigh kanalı olduğu durumlar için A-UZBK ve Alamouti FK-UZBK yöntemleri ile kodlanmış DFBÇ için elde edilen bit-hata-oranlarını sunmuştur. Yapılan çalışmalarda görülmüştür ki her ne kadar da DFBÇ semböller arası karışmaları hafifleterek tek başına iyi bir performans gösterse de, DFBÇ’nin Alamouti UZBK gibi bir gönderim çeşitleme tekniği ile birleşiminden elde edilecek bağlantı düzeyi bit-hata-oranları daha da iy olmaktadır. Simülasyon sonuçları KDB’nin mevcut olmadığı ve FK-UZBK’nin kullanımının gerekli olduğu durumlarda sistem performansının 10-4 bit-hata-oranında yaklaşık olarak 2.2 dB gerilediğini göstermiştir (ikili faz kaydırmalı kipleme kullanan UZBK-DFBÇ ile karşılaştırıldığında). Anahtar Kelimeler: UZBK, Diferansiyel UZBK, DFBÇ, Çoklu-Çıkış, Rayleigh Zayıflama.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2013. Supervisor: Assoc. Prof. Dr. Erhan A. İnce.
Keywords: Electrical and Electronic Engineering; Wireless Communication Systems; Orthogonal frequency division multiplexing; STBC, DSTBC, OFDM, Rayleigh Fading, BER